2022
DOI: 10.1007/s12609-022-00450-6
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Margin Trials in Breast Cancer

Abstract: Purpose of Review Obtaining negative margins in breast conservation surgery continues to be a challenge. Re-excisions are difficult for patients and expensive for the health systems. This paper reviews the literature on current strategies and intraoperative clinical trials to reduce positive margin rates. Recent Findings The best available data demonstrate that intraoperative imaging with ultrasound, intraoperative pathologic assessment such as frozen sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…A variety of alternative localization techniques have been developed to address these flaws. Radio-occult lesion localization (ROLL) comprises injection of a radioactive colloid into the tumour, whereas a radioactive seed is implanted in radioactive seed localization (RSL) 2 , 3 , 7 , 8 . A Cochrane Review 7 confirmed that WGL is comparable to RSL and ROLL in terms of positive margins and reoperation rates, but the latter are associated with improved patient comfort, hospital flow, or surgical precision.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of alternative localization techniques have been developed to address these flaws. Radio-occult lesion localization (ROLL) comprises injection of a radioactive colloid into the tumour, whereas a radioactive seed is implanted in radioactive seed localization (RSL) 2 , 3 , 7 , 8 . A Cochrane Review 7 confirmed that WGL is comparable to RSL and ROLL in terms of positive margins and reoperation rates, but the latter are associated with improved patient comfort, hospital flow, or surgical precision.…”
Section: Resultsmentioning
confidence: 99%
“…A Cochrane Review 7 confirmed that WGL is comparable to RSL and ROLL in terms of positive margins and reoperation rates, but the latter are associated with improved patient comfort, hospital flow, or surgical precision. More recently, a ferromagnetic seed (Magseed ® ; Endomag, Cambridge, UK), a reflector to electromagnetic radar signals (SAVI SCOUT ® ; Meritmedical, South Jordan, UT, USA), a radiofrequency tag (Localizer™; Hologic, Marlborough, MA, USA), and an electromagnetic signature for triangulation (Elucent Smart Clip™; Elucent Medical, Eden Prairie, MN, USA; NCT04604561) have entered the market 2 , 3 , 8–10 . Seldom used techniques include cryo-assisted localization (freezing) and carbon track localization (intralesional carbon injection), which enable tactile and visual feedback, respectively 8 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an overwhelming need to improve precision during BCS, 10 , 44 47 but current localizing techniques are unable to provide surgeons with sufficient information to guarantee entire tumor removal. 12 Eliminating the need for a second surgery would benefit patients, alleviating psychological stress, reducing complications, and improving cosmetic outcomes and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Several new approaches for intraoperative tumor margin detection have been proposed during the recent years [19,20]. A new real-time in situ tissue differentiation method is optical emission spectroscopy (OES) [21][22][23].…”
Section: Introductionmentioning
confidence: 99%